Ideology and political development : the growth and development of political ideas in the Caribbean 1774-1983 - Benn, Denis (UWI. Institute of Social and Economic Research KingstonJM, 1987)
Traces the development of political ideas in the Caribbean during 1774-1977. Examines the constitutional evolution of the Old Representative System and analyses theory of Crown Colony Government. Discusses the intellectual elements embodied in the development of West Indian nationalist consciousness with emphasis on the writings of Eric Williams. Reviews development of the theory of plantain economy and society. Examines development of the marxist tradition (focusing on C.L.R. James and Cheddi Jagan) and of black consciousness.